Secukinumab provides better relief from the impact of psoriasis on daily activities and personal relationships than etanercept: results of two phase 3 placebo-controlled randomized clinical trials in moderate-to-severe psoriasis. (4th July 2017) - Korman, Neil J.; Sofen, Howard; Fretzin, Scott; Rich, Phoebe; Zhao, Yang; Herrera, Vivian; Nyirady, Judit; Williams, Nicole; Mordin, Margaret; Tyring, Stephen
Abstract: Background: Psoriasis can greatly impact patients' lives, influencing what clothing they wear and impairing their sexual functioning. Objective: To provide a detailed comparison of the impact of secukinumab vs. etanercept on enabling patients with psoriasis to have more normal lives with respect to daily activities (DA) (e.g. choosing clothing) and personal relationships (PR) (e.g. sexual functioning). Methods: Baseline to Week 52 ERASURE and FIXTURE data for secukinumab 300 mg and etanercept were analyzed. Treatment differences in mean scores on the DA and PR subscales and items from the Dermatology Life Quality Index were compared. The proportions of subscale and item responders (score = 0) were compared. Results: Subjects receiving secukinumab ( n  = 572) achieved greater mean improvement in DA and items (q3 and q4) than subjects receiving etanercept ( n  = 326; all p  < .01 through Week 52). Subjects receiving secukinumab achieved greater mean improvement in PR and items (q8 and q9) than subjects receiving etanercept (subscale: p  < .05 at Weeks 8 and 12). Response rates were significantly higher for secukinumab than for etanercept for DA (all p  < .0001) and PR (all p  < .05 except Weeks 4 and 36). Conclusions: Secukinumab 300 mg provides greater improvements and more effective relief from psoriasis impact on DA and PR than etanercept.